SCREENING OF SELECTED PLANT ESSENTIAL OILS FOR THEIR ANTIFUNGAL ACTIVITY AGAINST CANDIDA SPECIES ISOLATED FROM DENTURE STOMATITIS PATIENTS - Bhat, Vinaya; Sharma, S.M.; Shetty, Veena; Shastry, C.S.; Rao, Vaman; Shenoy, Shilpa M.; Saha, Santanu; Balaji, Sriram (Journal of Health and Allied Sciences NU, 2014)
Background: Many efforts have been made to discover new antimicrobial compounds from various sources such as micro-organisms, animals and plants. Use of herbal medicines has a long history in Asian population in treating different ailments. Many plants have been found to have properties like antibacterial, antifungal and antioxidant activities.In a complete denture wearer, due to either local or systemic factors, denture stomatitis has been found to a have high prevalence. In such patients, higher incidence of Candida infection and increased levels of Candida spp. also have been identified. Existing antifungal agents like Nystatin & Fluconazole have been found to have toxic effects on long term application and chances of development of drug resistance is high. Medicinal plants have been used to inhibit growth and development of fungal infection from Candida isolated from sites other than oral cavity.Objectives: To evaluate the antifungal activity of some of the medicinal essential oils against oral isolates of Candida obtained from denture wearing patients identified through a survey.Materials and Methods: The oral isolates of Candida species were collected after conducting a survey of complete denture wearers, wearing the denture for at least more than a year. The speciation of the organism was done after identifying it from the specimens. It was confirmed with the help of germ tube test, other biochemical tests and chlamydospore formation tests. A lab isolate also was included in the study. The essential oils of different herbs were extracted using hydro distillation methods. The antifungal activity of these oils was tested and compared with antifungal activity of Nystatin and fluconazole using modified Kirby-Baeur method. The inhibition zones of different oils were measured and compared among themselves against all the clinical isolates and the lab isolate.Results: About 55 complete denture wearing patients have been surveyed and among them 27 have been found to be positive for Candida-associated denture stomatitis. Among the Candida species, Candida albicans was more prevalent followed by C. tropicalis and C. glabrata.Among the test essential oils, Origanum vulgare (stored & fresh) and clove oil gave positive results against all isolates. The fresh samples gave better results than the stored and all three oils showed more antifungal activity than Nystatin & fluconazole.Interpretation: The candida-associated denture stomatitis is prevalent in patients who are wearing denture prosthesis for more than a year.Candida albicans is the most prevalent causative species followed by C. tropicalis and C. glabrata.Origanum vulgare and clove oil are potent antifungal agents against oral species of Candida. They can be either used separately or their synergistic activity could be explored against denture stomatitis.
Keywords: Denture stomatitis; herbal essential oils; clove oil; origanum vulgare; Candida spp; nystatin; fluconazole